2016
DOI: 10.1093/mnras/stw086
|View full text |Cite
|
Sign up to set email alerts
|

Orbital dynamics of exoplanetary systems Kepler-62, HD 200964 and Kepler-11

Abstract: The presence of mean-motion resonances (MMRs) in exoplanetary systems is a new exciting field of celestial mechanics which motivates us to consider this work to study the dynamical behaviour of exoplanetary systems by time evolution of the orbital elements of the planets. Mainly, we study the influence of planetary perturbations on semimajor axis and eccentricity. We identify (r + 1) : r MMR terms in the expression of disturbing function and obtain the perturbations from the truncated disturbing function. Usin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 22 publications
(30 reference statements)
0
9
0
Order By: Relevance
“…Five of the six planets transit their star, but the secondoutermost planet was discovered with the radial velocity technique (Buchhave et al 2016). Kepler-11's and Kepler-20's stellar ages have been estimated at 3.2±0.9 Gyr (Bedell et al 2017) and 7.6±3.7 Gyr (Buchhave et al 2016), respectively, indicating that each system is long-term stable (see also Migaszewski et al 2012;Mahajan & Wu 2014;Hands et al 2014;Mia & Kushvah 2016;Jontof-Hutter et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Five of the six planets transit their star, but the secondoutermost planet was discovered with the radial velocity technique (Buchhave et al 2016). Kepler-11's and Kepler-20's stellar ages have been estimated at 3.2±0.9 Gyr (Bedell et al 2017) and 7.6±3.7 Gyr (Buchhave et al 2016), respectively, indicating that each system is long-term stable (see also Migaszewski et al 2012;Mahajan & Wu 2014;Hands et al 2014;Mia & Kushvah 2016;Jontof-Hutter et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The residuals between the theoretical velocity and the data are shown in the bottom panel. (Wittenmyer et al 2012), investigated in more detail the resonant behavior exhibited for the reported parameters (Mia & Kushvah 2016) and investigated other, more complex scenarios for the formation of HD 200964 (Emel'yanenko 2012, Tadeu dos Santos et al 2015 4. METHODS In this work, in addition to analyzing a baseline of data longer than that used in JPH11, we investigate the underlying posterior by explicitly conditioning our Markov chain Monte Carlo (MCMC) search on longterm stability.…”
Section: Previous Analysismentioning
confidence: 99%
“…Few planetary systems are discovered containing at least one earth like planet where life can exist. For example Kepler-62 (Borucki et al, 2013;Mia and Kushvah, 2016a), Kepler-186 (Bolmont et al, 2014), Kepler-69 (Barclay et al, 2013) and HD 40307 (Tuomi et al, 2013) systems consist at least one earth like planet in the habitable zone. Among about 5000 newly discovered exoplanetary systems only few systems found in mean motion resonances(MMRs).…”
Section: Introductionmentioning
confidence: 99%